An ice sheet wide framework for radar-inference of englacial attenuation and basal reflection with application to Greenland - Jordan,T; Bamber,J; Williams,C; Paden,J; Siegert,MJ; Huybrechts,P; Gagliardini,O; Gillet-Chaulet,F (Cryosphere, 2016)
Radar inference of the bulk properties of glacierbeds, most notably identifying basal melting, is, in general,derived from the basal reflection coefficient. On the scale ofan ice sheet, unambiguous determination of basal reflectionis primarily limited by uncertainty in the englacial attenuationof the radio wave, which is an Arrhenius function oftemperature. Existing bed-returned power algorithms for derivingattenuation assume that the attenuation rate is regionallyconstant, which is not feasible at an ice-sheet-wide scale.Here we introduce a new semi-empirical framework for derivingenglacial attenuation, and, to demonstrate its efficacy,we apply it to the Greenland Ice Sheet. A central featureis the use of a prior Arrhenius temperature model to estimatethe spatial variation in englacial attenuation as a firstguess input for the radar algorithm. We demonstrate regionsof solution convergence for two input temperature fields andfor independently analysed field campaigns. The coverageachieved is a trade-off with uncertainty and we propose thatthe algorithm can be “tuned” for discrimination of basal melt(attenuation loss uncertainty ∼ 5 dB). This is supported byour physically realistic (∼ 20 dB) range for the basal reflectioncoefficient. Finally, we show that the attenuation solutioncan be used to predict the temperature bias of thermomechanicalice sheet models and is in agreement with known modeltemperature biases at the Dye 3 ice core.